Coastal and marine environmental education : a study of community involvement in the Westfjords of Iceland and Southern New Zealand - Wilke, Maria, 1987- (2019)
Verkefnið er lokað til 17.06.2020. Coastal communities are among the most vulnerable to climate change and other anthropogenic impacts on the environment. Adaptive community-driven resource management is vital to build resilience. Only communities committed to ongoing learning can adapt to a continuously changing environment. This is why environmental education (EE) should be community-focussed and part of coastal and marine management. Key informants were interviewed in Ísafjörður in the Westfjords of Iceland to gather perceptions about local coastal and marine environmental issues and EE. Resulting statements were then tested on the wider community via an online survey. From the survey results, opportunities for EE were identified. They formed the basis for studying through an action research approach several best practice examples of EE in coastal New Zealand where such programmes are more established than in Iceland. The results from both sites suggested a lack of political empowerment perceived by community members, a narrow focus of EE target groups and a lack of collaboration between providing institutions of EE. Recommendations are made on how to further links between EE and community-driven management in the study sites and beyond by widening target audiences and creating communal learning platforms supporting transparent communication. By offering community-focussed EE, coastal communities can become more empowered and adaptive in community-driven marine resources management.